2015
DOI: 10.12806/v14/i3/r5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transformational Leadership Practices: Implications for School Districts and Principal Preparation Programs

Abstract: The purpose of this study was to determine the leadership practices needed to improve academic achievement and generate positive change in school organizations. The study was also conducted to provide insight to principal preparation programs and school districts about effective transformational leadership practices. A quantitative research method was used to achieve the survey study. Ninety-two teachers completed the Leadership Practices Inventory developed by Kouzes and Posner. Data was analyzed with the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 24 publications
(49 reference statements)
2
31
0
1
Order By: Relevance
“…The findings indicated a high positive correlation between faculty perceptions of principals and principal behaviors on all five pillars of the LPI survey (challenge the process .87, inspire a shared vision .89, enabling others to act .96, modeling the way .83, encouraging the heart .90, and composite .88; Pugh et al, 2011) Oumthanom (2001) found that mean scores on the LPI (p < .05; adjusted R 2 ¼ .03, F(1, 94) ¼ 4.11, p ¼ .05) for principals were higher than teachers' mean scores as they related to the leadership practices of principals. A study of teachers' perceptions of the leadership practices of school principals measuring the differences in the leadership practices of principals in high and low performing schools found that there were significant differences within the five leadership practices for high and low performing school principals (Quinn, Deris, Bischoff, & Johnson, 2015). The LPI survey observer form used to measure middle and high school teachers' perceptions of their educational leaders found that there were no significant differences between middle and high school teacher perceptions of principals (Leech & Fulton, 2002).…”
Section: Organizational and School Changementioning
confidence: 99%
“…The findings indicated a high positive correlation between faculty perceptions of principals and principal behaviors on all five pillars of the LPI survey (challenge the process .87, inspire a shared vision .89, enabling others to act .96, modeling the way .83, encouraging the heart .90, and composite .88; Pugh et al, 2011) Oumthanom (2001) found that mean scores on the LPI (p < .05; adjusted R 2 ¼ .03, F(1, 94) ¼ 4.11, p ¼ .05) for principals were higher than teachers' mean scores as they related to the leadership practices of principals. A study of teachers' perceptions of the leadership practices of school principals measuring the differences in the leadership practices of principals in high and low performing schools found that there were significant differences within the five leadership practices for high and low performing school principals (Quinn, Deris, Bischoff, & Johnson, 2015). The LPI survey observer form used to measure middle and high school teachers' perceptions of their educational leaders found that there were no significant differences between middle and high school teacher perceptions of principals (Leech & Fulton, 2002).…”
Section: Organizational and School Changementioning
confidence: 99%
“…The multivariate analysis revealed that 34% of the mathematics achievement of pupils could be explained through social contexts of learning. Quin, Deris, Bischoff, and Johnson (2015) investigated the correlation between leadership, culture, and student achievement in elementary, middle, and high schools. 216 teachers from 31 schools were selected as a sample Rhoden ( 2012) conducted an ex-post facto study and found that student achievement was significantly correlated with head teachers' leadership behavior and school climate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, several obstacles interfere with the creation of equity-oriented leaders. First, most practicing principals are not equipped with the knowledge or skills to become these kinds of leaders (Darling-Hammond, Meyerson, LaPointe, & Orr, 2010;Quin, Deris, Bischoff, & Johnson, 2015). Furthermore, despite a significant investment in educational leadership preparation programs, this same literature also suggests that many traditional and alternative preparation programs do not adequately prepare prospective school leaders for equity-oriented, inclusive leadership (Darling-Hammond et al, 2010;Quin et al, 2015).…”
Section: Wicked Problems Frameworkmentioning
confidence: 99%
“…First, most practicing principals are not equipped with the knowledge or skills to become these kinds of leaders (Darling-Hammond, Meyerson, LaPointe, & Orr, 2010;Quin, Deris, Bischoff, & Johnson, 2015). Furthermore, despite a significant investment in educational leadership preparation programs, this same literature also suggests that many traditional and alternative preparation programs do not adequately prepare prospective school leaders for equity-oriented, inclusive leadership (Darling-Hammond et al, 2010;Quin et al, 2015). It is no wonder, then, that many acting school leaders struggle to maintain a focus on equity and inclusion (Billingsley & McLeskey, 2014;Cambron-McCabe & McCarthy, 2005;DiPaola & Walther-Thomas, 2003), particularly when juggling competing demands and complex political climates.…”
Section: Wicked Problems Frameworkmentioning
confidence: 99%